Eremophilane-Type Sesquiterpenoids From the Endophytic Fungus Rhizopycnis vagum and Their Antibacterial, Cytotoxic, and Phytotoxic Activities - Wang, Ali; Yin, Ruya; Zhou, Zhiyao; Gu, Gan; Dai, Jungui; Lai, Daowan; Zhou, Ligang (Frontiers in Chemistry, 2020)
Fourteen new eremophilane-type sesquiterpenoids, named rhizoperemophilanes AN (114), together with eight known congeners, were isolated from the culture of the endophytic fungus Rhizopycnis vagum. The structures of the new compounds were elucidated by extensive spectroscopic analyses, as well as ECD calculations and the modified Mosher's method for the assignment of the absolute configurations. Rhizoperemophilane J (10) contains an uncommon C-4/C-11 epoxy ring, while rhizoperemophilane N (14) features an unprecedented 3-nor-eremophilane lactone-lactam skeleton. These metabolites were evaluated for their antibacterial, cytotoxic, and phytotoxic activities. Among them, compounds 11, 16 and 20 displayed antibacterial activities, while 14 showed selective cytotoxicity against NCI-H1650 and BGC823 tumor cells. Moreover, compounds 5, 6, 12, 13, 16 and 19 exhibited strong phytotoxic activities against the radicle elongation of rice seedlings.